Microwave Imaging of a Slightly Varying 2-D Conducting Object Through Generalized Impedance Boundary Conditions - Aslanyurek, Birol; Sahinturk, Hulya; Cayoren, Mehmet (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2014)
We consider reconstructing the shape of a perfect electric conducting object and developed a novel imaging method based on generalized impedance boundary conditions (GIBCs). The method relies on selecting a fictitious surface encircling the unknown object in which the surface impedance is reconstructed from the scattered field measurements. Later, the shape reconstruction problem is cast into an equivalent problem where the distance variation between the fictitious impedance surface and the unknown target is determined from the reconstructed surface impedance. Since the performance of the method depends on the selection of the impedance surface, we present a selection criterion according to the validity conditions of GIBCs. The method is capable of reconstructing both convex and concave structures whose shape deviates, at most, a tenth of the wavelength from the impedance surface, as demonstrated with numerical results.
Keywords: Generalized impedance boundary conditions (GIBCs); inverse scattering problems; shape reconstruction; SCATTERING; TARGETS; Geochemistry & Geophysics; Engineering; Remote Sensing; Imaging Science & Photographic Technology